Data supporting: 'Comparative economics of Sida hermaphrodita (L.) Rusby and Silphium perfoliatum L. as bioenergy crops in Europe' - Cumplido-Marín, Laura; Graves, Anil (Cranfield University, 2022)
Financial models for the UK and 3 European countries (Italy, Germany, Poland) produced using the Net Present Value Approach and added sensitivity analysis, comparing the establishment and production of Sida hermaphrodita and Silphium perfoliatum with other arable and energy crops. All models work on a left-to-right logic, very intuitive to follow. Disclaimer: the author /s are not responsible for any further uses of the models or decisions made after the results presented in the models.
Keywords: Economic Modeling'; 'agribusiness economics'; 'bioenergy feedstock production'; 'sensitivity analysis accounting'; 'comparative analysis'; 'Agricultural Economics'; 'Crop and Pasture Biomass and Bioproducts'